A comprehensive study of the effect of bipolar plate (BP) geometry design on the performance of proton exchange membrane (PEM) fuel cells. (September 2019) - Wilberforce, Tabbi; El Hassan, Zaki; Ogungbemi, Emmanuel; Ijaodola, O.; Khatib, F.N.; Durrant, A.; Thompson, J.; Baroutaji, A.; Olabi, A.G.
Abstract: Fuel cell efficiency is determined by many factors, including operational parameters such as electrochemical kinetics, cell operating temperature, mass transport, flow rates and other physical components in the cell stack like the membrane electrode assembly (MEA) as well as the bipolar plate (BP). The BP accounts for almost 70% of the mass of the stack and 30% of the overall price of the cell stack on the fuel cell market. The bipolar plate geometry design serves as the medium of entry of the reactive gases into the fuel cell and also functions as a platform for easy dissemination of the reactive substance onto the active surface of the cell stack. Its crucial role in the stack determines water management for the PEM fuel cell, thermal and electrical conductivity, mass transport and current density distribution. This research therefore aims to make a critical assessment of existing bipolar plate geometry design with respect to the maximum functionality of fuel cell (advantages and disadvantages of each design considered). The work thoroughly discusses some parameters that define an effective bipolar plate geometry design which is able to enhance the functionality of a cell stack. Furthermore, the work will serve as a guide to the fuel cell research community in the selection of a suitable geometry design for any fuel cell operating at varying conditions. Highlights: Efficiency of a fuel cell using different types of bipolar plate is discussed. Merit and demerit of each type of bipolar plate geometry design is reported. Effect of operational conditions on these types of bipolar plate geometry is captured. Comparison between the types of fuel cell bipolar plate geometry designs from literature is also discussed.